Budget Cuts in Scholastic Media: A Focus Group Study of Oklahoma Journalism Advisers' Survival Skills. (September 2019) - Wilderman, Melanie; Nasrin, Sohana; Davis, Jeremy
Scholastic journalism plays an important role in future professional journalism. Due to journalism's place in a functioning democracy, journalism education is also tied to a democracy's success. Many U.S. states have cut budgets severely for public education, which heavily affects subjects such as journalism. Researchers interviewed 14 scholastic journalism advisers in Oklahoma, concerning how student publications function amid financial cuts. Results indicate advisers engaging in innovative teaching and collaboration due to budget cuts, finding ways for publications to connect and be useful for schools and communities, and advisers' fears and concerns due lack of support and ever-decreasing funding obstacles.